Investigating the effect of servqual dimensions on customer satisfaction among tourists who visited resort hotels in Perak, Malaysia - Lee, Joe Wai Hong; Loh, Wei Hong (2024)
This research applies the SERVQUAL dimensions including tangible, assurance, reliability, responsiveness and empathy to examinate their effect on customer satisfaction towards resort hotels located in Perak, Malaysia. The purpose of this study is to close the gap on the lack of research regarding Perak resort hotels by providing better insight into factors affecting customer satisfaction. The findings are expected to contribute to understanding what customers expect. This is quantitative research consisting of 390 participants who visited and stayed at Perak resort hotels before. The judgemental technique is employed to find suitable respondents. The questionnaire was designed using Google Forms and contains four sections. The data that has been collected is analysed utilising the SPSS software. The results show that each dimension (tangible, assurance, reliability, responsiveness and empathy) has a significant impact on customer satisfaction. Furthermore, empathy was the most important predictor of customer satisfaction compared to other dimensions. Keywords: Tangible, Reliability, Responsiveness, Assurance, Empathy, Customer Satisfaction, Resort, Perak HF5410-5417.5 Marketing. Distribution of products